2007
DOI: 10.1523/jneurosci.4430-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Hippocampal Nuclear Factor-κB by Retrieval Is Required for Memory Reconsolidation

Abstract: Initially, memory is labile and requires consolidation to become stable. However, several studies support that consolidated memories can undergo a new period of lability after retrieval. The mechanistic differences of this process, termed reconsolidation, with the consolidation process are under debate, including the participation of hippocampus. Up to this point, few reports describe molecular changes and, in particular, transcription factor (TF) involvement in memory restabilization. Increasing evidence supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 39 publications
5
77
1
Order By: Relevance
“…This recovery depended on memory reactivation, and only occurred if the treatment was administered within a temporal window. Besides, to provide compelling evidence that Ch acts specifically on the mechanisms mediating memory reconsolidation, as opposed to producing nonspecific effects, it is necessary to show that the change does not occur shortly after retrieval, but is observed later (Boccia et al, 2007;Nader et al, 2000). Along this line, we observed that Ch was effective only when T2 was delayed enough from T1.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This recovery depended on memory reactivation, and only occurred if the treatment was administered within a temporal window. Besides, to provide compelling evidence that Ch acts specifically on the mechanisms mediating memory reconsolidation, as opposed to producing nonspecific effects, it is necessary to show that the change does not occur shortly after retrieval, but is observed later (Boccia et al, 2007;Nader et al, 2000). Along this line, we observed that Ch was effective only when T2 was delayed enough from T1.…”
Section: Discussionmentioning
confidence: 72%
“…However, to add evidence that the pharmacological actions of Ch are exerted on memory reconsolidation the effects of Ch should not be seen in a retention test performed shortly after retrieval, as was already shown blocking protein synthesis (Nader, Schafe, & LeDoux, 2000) and using NF-B inhibitors (Boccia et al, 2007).…”
Section: The Effects Of Ch On Memory Are Not Disclosed Shortly After mentioning
confidence: 99%
“…Short-term memory was not affected by post-retrieval intra-hippocampal injections of κBdecoy, whereas its effect on LTM persisted for more than 3 weeks, C.M. Baratti et al www.bjournal.com.br without signs of spontaneous recovery (13).…”
Section: Nuclear Factor κ κ κ κ κB Transcription Factormentioning
confidence: 89%
“…NF-κB is also activated in the hippocampus by memory retrieval, and is probably involved in restabilization of the original memory, but its activation occurs earlier in memory reconsolidation than in memory consolidation: the peak of NF-κB activation takes place 15 min after memory reactivation (13).…”
Section: Nuclear Factor κ κ κ κ κB Transcription Factormentioning
confidence: 99%
See 1 more Smart Citation